230k views
5 votes
6 ÷ 2(1+2) ÷ 4(4+5) ÷ 6 =​

User Theodore
by
5.4k points

2 Answers

2 votes

Answer:


3(3)/(8)

Explanation:

6 ÷ 2(1+2) ÷ 4(4+5) ÷ 6 =​

----------------------------------------

By order of operations, parentheis comes first.

6 ÷ 2*(1+2) ÷ 4*(4+5) ÷ 6 =​

6 ÷ 2*(3) ÷ 4*(9) ÷ 6=

----------------------------------------

Next comes multiplication and division. Now, we can remove the parentheis and solve from left to right.

6 ÷ 2*(3) ÷ 4*(9) ÷ 6=

6 ÷ 2*3 ÷ 4*9 ÷ 6=

3*3 ÷ 4*9 ÷ 6=

9 ÷ 4*9 ÷ 6=

27/8=


3(3)/(8)

User Gcstr
by
5.3k points
3 votes

Answer:

The answer to this equation is 7.5

Explanation:

What I did is started with PEMDAS:

6÷2 (1 + 2) ÷4 (4 + 5) ÷ 6

^ ^

(3) (9)

Now the 3 and the 9 are what are in the ()

6÷2 = 3... 3 (3) = 9.

9 ÷ 4 = 5.

The 9 from earlier is still in parenthesis...

Take 5 and the 9 in parenthesis and multiply (If a single number is in (), It means to multiply anyway)

5 (9) = 45

The Final Step is to divide by 6

45 ÷ 6 = (FINAL) 7.5

I hope this helped! (:

User SFernando
by
4.6k points